The official guide for GMAT review 2015 - Graduate Management Admission Council (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
Reviews topics covered on the verbal, quantitative, and integrated reasoning portions of the test; provides test-taking strategies; and includes a diagnostic test with answers and detailed explanations.
"The most comprehensive study guide, from the creators of the test."
Keywords: Graduate Management Admission Test -- Study guides